Exploring the influence of guiding feedback on mathematical self-efficacy: Insights from a field study with engineering students - Razeghpour, Farhad (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
Feedback is considered a critical factor in supporting learners' self-efficacy. In the context of digital tasks with so-called guiding feedback, students receive error-specific hints and are offered sub-steps in case of incorrect answers. After receiving the feedback, students can immediately use it to correct their answers. Based on theoretical considerations, positive effects of guiding feedback on students' self-efficacy are assumed. Therefore, we conducted a field study involving 222 engineering students in which we offered them voluntary tasks with guiding feedback. The results indicate that students who worked on these tasks did not show significantly higher self-efficacy afterwards than students who worked less or even not at all on these tasks. However, it was found that students who used this offer had significantly higher self-efficacy in tasks with guiding feedback than in tasks for which this feedback was not provided.